At your service, Madam (Sir)! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
At your service, Madam (Sir)!How do I stop black spots developing on mango slices when drying them in a solar drier? How can we write up a business plan for our cooperative s fish canning plant? How can we certify our produce as organic? Which...